POLITIK HUKUM BATAS USIA PASANGAN CALON PRESIDEN DAN WAKIL PRESIDEN BERDASARKAN PUTUSAN MK NOMOR 90/PUU-XXI/2023 - Usman; Setiadi, Wicipto (Bawaslu Provinsi Jawa Barat, 2023)
This research aims to analyze juridically the legal politics of the age limit for presidential candidates in Indonesia based on the Constitutional Court's decision Number 90/PUU-XXI/2023 and what the ideal age limit for presidential and vice-presidential candidates is because this is interrelated with ongoing democracy in Indonesia and other problems. problems related to the age limit for presidential candidates in the 2004 election. The research method used is through a normative legal approach or doctrinal legal research which is aimed only at written regulations or other legal materials with an approach that results in conclusions. The law does not provide a minimum or maximum age limit for presidential candidate pairs, so the provisions of Article 169 of Law 7 of 2017 concerning Elections provide a maximum age limit of 40 (forty) years to become a presidential candidate pair which is then registered by a combination of political parties with the General Election Commission. . General for use as presidential candidate pairs, which should change the norms in article 169, not only limiting the minimum age of presidential candidate pairs, but the maximum limit should be the focus of the Constitutional Court in understanding the norms of this article, in which case the Constitutional Court is considering the option of adding new norms regarding limits. maximum age to ensure legal certainty.